Handbook of Business Communication Linguistic Approaches. - Mautner, Gerlinde (Handbooks of Applied Linguistics [HAL], 2016)
The Handbooks of Applied Linguistics provide a state-of-the-art description of established and emerging areas of Applied Linguistics. Each volume gives an overview of the field, explains the most important traditions and their findings, identifies the gaps in current research, and gives perspectives for future directions.